Assessment of Water, Sanitation and Hygiene Services in Sub-Saharan Africa - Ohwo, Odafivwotu; Agusomu, Tano Dumoyei (European Scientific Journal, ESJ, 2018)
Adequate provision of water, sanitation and hygiene (WASH) facilities are supporting pillars of healthy living. Hence, this review was aimed at the assessment of the status of WASH services in sub-Saharan Africa. The study used secondary data, sourced from the Joint Monitoring Programme (JMP) report by UNICEF and WHO (2015). This data was used to assess the WASH status of sub-Saharan Africa. Other information highlighted in the paper were obtained from existing literature, in peer reviewed journals, conference proceedings, commissioned studies and the internet. Data obtained were presented in tables and further analyzed using percentages. The review revealed thatWASH services are poorly provided in sub-Saharan Africa, with negative consequencies on the health and socio-economic development of people who have poor access to WASH services. Some of the reasons that have led to the poor provision of WASH services in the region are broadly classified into natural and human-related. The natural causes are the region’s extreme climate and rainfall variability, which has been made worst by climate change, resulting in desertification, shrinkage of some water bodies and growing water scarcity; while the human-related causes include, poor governance, weak institutions, poor financing, and corruption in the WASH sector, amongst others. The study recommends the adoption of a comprehensive, inclusive and integrated WASH strategy that fit the peculiarities of each country in the region. This would help in maximizing the benefits of WASH services and the promotion of healthy living in the region.